The Biological Effects of Diagnostic Cardiac Imaging - Landini, L.; Ripoli, A.; Santarelli, M. F.; Landini Jr., L.; Positano, V. (Current Pharmaceutical Design, 2009)
In this paper the authors deal with the main imaging techniques available to clinical cardiologists, with a brief overview of biophysical and biological aspects which are of relevance for the assessment of health effects related to the exposure of patients to both ionizing and non ionizing radiation. A main contribute is the reviewing published evidence on biological effects of radiation, trying to compose a balanced issue in order to increase awareness and knowledge about radiation exposure from cardiac imaging and implications for health risk.
Keywords: non-ionizing radiation